Practical Tools Review Based on Physics, Chemistry, and Biology Parameters to Train Systems Thinking Skills - Nur Ainun Hariyanto; Kartini Herlina; Chansyanah Diawati; M. Setyarini (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to develop an integrated practical tool for water pollution, covering physics, chemistry, and biology parameters to enhance students' systems thinking skills. Using the 4D development model (Define, Design, Develop, Disseminate), this R&D study identifies a critical gap: 94% of teachers are unfamiliar with pH-4502C sensors, and 78% do not recognize systems thinking indicators. The developed tool integrates digital sensor technology for real-time water quality monitoring. Expert validation and teacher trials indicate the product is highly effective, with 83% of educators agreeing it facilitates the training of systems thinking at levels A, B, and C. The results show a significant improvement in students' ability to identify system components and analyze dynamic interrelationships compared to conventional methods. It is concluded that this integrated tool successfully bridges the technological gap in junior high school labs while providing a concrete framework for mastering higher-order thinking skills in environmental education.